Urbanity and Gender: - Sofia Rodrigues Boito (Revista Brasileira de Estudos da Presença, 2024)
Urbanity and Gender: what displaces a walking body? – This article explores the relation between body and urban displacement from an intersectional feminist perspective. Based on recent studies on urbanity and gender – feminisms, art and public space – we will analyze modern and contemporary artistic practices in the city, considering the friction between gendered bodies and the city. The aim is to discuss the displacement that certain bodies establish when walking freely through the urban space.